2020
DOI: 10.33393/abtpn.2020.2030
|View full text |Cite
|
Sign up to set email alerts
|

Budget impact analysis of pegfilgrastim biosimilar in the treatment of febrile neutropenia in Italy

Abstract: Introduction: Granulocyte-colony stimulating factors (G-CSFs) can significantly reduce the risk of febrile neutropenia (FN) among certain patients receiving chemotherapy. FN is associated with significant clinical and nonclinical complications. At present, the patent protection of pegfilgrastim (Neulasta®) has expired, and a biosimilar (Ziextenzo®) has been approved. Since the biosimilar price is expected to be lower as compared with the originator’s, the present Drug Budget Impact analysis tries to evaluate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The analysis highlighted the economic advantage of using pegfilgrastim biosimilars in place of SA G-CSF treatments in the FN treatment setting, providing a substantial cumulative A confirmation of our analysis comes from the results of a budget impact model built by Ravasio et al [21] in order to assess the economic impact generated in Italy from the use of the pegfilgrastim biosimilar compared to the originator. These authors showed that the availability of the biosimilar could (in five years) generate cumulated savings as high as € 6.4 million for the whole Italian NHS [21]. However, this analysis did not calculate the potential savings of the introduction of pegfilgrastim biosimilar to the local formulary, compared to SA and LA G-CSFs currently used for FN prophylaxis.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The analysis highlighted the economic advantage of using pegfilgrastim biosimilars in place of SA G-CSF treatments in the FN treatment setting, providing a substantial cumulative A confirmation of our analysis comes from the results of a budget impact model built by Ravasio et al [21] in order to assess the economic impact generated in Italy from the use of the pegfilgrastim biosimilar compared to the originator. These authors showed that the availability of the biosimilar could (in five years) generate cumulated savings as high as € 6.4 million for the whole Italian NHS [21]. However, this analysis did not calculate the potential savings of the introduction of pegfilgrastim biosimilar to the local formulary, compared to SA and LA G-CSFs currently used for FN prophylaxis.…”
Section: Discussionsupporting
confidence: 65%
“…The recent licensing in Europe of biosimilar pegfilgrastim-containing products offers the opportunity to deliver the additional advantages of long-over short-acting G-CSF at a reduced cost. For countries currently using reference pegfilgrastim, evident cost savings are reported by switching to biosimilar pegfilgrastim [18,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation